Expanding the toolbox of metabolically stable lipid prodrug strategies - Toti, Kiran S.; Pribut, Nicole; D’Erasmo, Michael; Dasari, Madhuri; Sharma, Savita K.; Bartsch, Perry W.; Burton, Samantha L.; Gold, Hannah B.; Bushnev, Anatoliy; Derdeyn, Cynthia A.; Basson, Adriaan E.; Liotta, Dennis C.; et al. (Frontiers in Pharmacology, 2023)
Nucleoside- and nucleotide-based therapeutics are indispensable treatment options for patients suffering from malignant and viral diseases. These agents are most commonly administered to patients as prodrugs to maximize bioavailability and efficacy. While the literature provides a practical prodrug playbook to facilitate the delivery of nucleoside and nucleotide therapeutics, small context-dependent amendments to these popular prodrug strategies can drive dramatic improvements in pharmacokinetic (PK) profiles. Herein we offer a brief overview of current prodrug strategies, as well as a case study involving the fine-tuning of lipid prodrugs of acyclic nucleoside phosphonate tenofovir (TFV), an approved nucleotide HIV reverse transcriptase inhibitor (NtRTI) and the cornerstone of combination antiretroviral therapy (cART). Installation of novel lipid terminal motifs significantly reduced fatty acid hepatic ω-oxidation while maintaining potent antiviral activity. This work contributes important insights to the expanding repertoire of lipid prodrug strategies for the delivery and distribution of nucleoside and nucleotide therapeutics.